Responding to health risks along the value chain - Chenevix Trench, Pippa; Narrod, Clare A.; Roy, Devesh; Tiongco, Marites (International Food Policy Research Institute, 2011)
This brief describes food safety risks along the value chain, identifies drivers of change, presents the risks posed to the poor by both food safety challenges and responses to them, and underscores the use of risk-based analysis to craft effective food safety policies that benefit both poor consumers and poor producers.